Dark matter content of ETGs and its relation to the local density of galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Nigoche-Netro, A.; Ramos-Larios, G.; Díaz, R.; de la Fuente, E.; Lagos, P.; Ruelas-Mayorga, A.; Mendez-Abreu, J.; Kemp, S. N.
Abstract: We study the behaviour of the dynamical and stellar mass inside the effective radius as function of local density for early-type galaxies (ETGs). We use several samples of ETGs - ranging from 19000 to 98000 objects - from the ninth data release of the Sloan Digital Sky Survey. We consider Newtonian dynamics, different light profiles and different initial mass functions (IMF) to calculate the dynamical and stellar mass. We assume that any difference between these two masses is due to dark matter and/or a non-universal IMF. The main results are: (i) the amount of dark matter (DM) inside ETGs depends on the environment; (ii) ETGs in low-density environments span a wider DM range than ETGs in dense environments; (iii) the amount of DM inside ETGs in the most dense environments will be less than approximately 55-65 per cent of the dynamical mass; (iv) the accurate value of this upper limit depends on the impact of the IMF on the stellar mass estimation.